Effect of home-based group conversation intervention using smartphone application on cognitive health and psychological well-being of older adults with subjective cognitive concerns in Japan: a randomized controlled trial protocol - Miura, Kumi Watanabe; Tokunaga, Seiki; Sekiguchi, Takuya; Sugimoto, Hikaru; Otake-Matsuura, Mihoko (Frontiers in Psychology, 2023)
Background: Social activity is a key component in the prevention of cognitive decline. However, face-to-face social intervention has limited accessibility. To address this issue, we developed the “Photo-Integrated Conversation Moderated by Application” (PICMOA), a home-based group conversation intervention using smartphones. This paper introduces the PICMOA intervention and the protocol of the ongoing randomized controlled trial (RCT) which aims to evaluate the effects of PICMOA on the cognitive functioning and psychological well-being of Japanese community dwelling older adults at the risk of cognitive function decline. Methods: This study uses a RCT design in two parallel group trials with 1:1 allocation. The participants are community dwelling older adults aged 65 years and above, living in an urban city in Japan, with subjective cognitive concerns. In total, 81 participants were allocated to the intervention or control groups. The intervention group receives 30 minutes of weekly PICMOA sessions at their home for 12 weeks. The PICMOA intervention consists of 1) a photo preparation period before the session and 2) a structured group conversation session talking about the photos which participants took according to a specific theme. The control group receives 30 minutes of weekly health education videos on a tablet device. The primary outcome is cognitive functioning at pre- and post-phases of the 12-week intervention measured using the Telephone Interview for Cognitive Status in Japanese, semantic and phonemic fluency tests, and the Digit Span Forward and Backward tests. The secondary outcomes are psychological and social aspects including mental status, well-being, loneliness, and social support. Discussion: Interest is growing in internet-based activities for preventing social isolation. However, the effect of remote conversation interventions on cognitive functioning remains unclear. This study addresses this issue. We hope to provide a new avenue for older adults' social participation.